Barriers towards research activities among academics in the chartered accountancy stream at the North-West University, South Africa: None - Sekgota, S. (South African Journal of Higher Education, 2024)
Generally, departments of accounting at universities in South Africa that are accredited by the South African Institute of Chartered Accountants (SAICA) mainly focus on teaching the syllabus as prescribed by the Institute. There is no research methodology module in this syllabus neither at undergraduate nor honours level. To qualify as a chartered accountant, one needs to pass an honours degree in accounting and write and pass two board exams. A qualified chartered accountant (CA/SA) will most likely encounter a research methodology module for the first time at master’s-degree level. Since 2008, in addition to teaching and learning and community engagement, the departments of accounting have embraced their scholarly activities, which include supervision and/or publishing. As a result, there is an increased effort by the departments of accounting to have its staff members with a chartered accountancy qualification to enrol for master’s and doctoral degrees (De Jager, Lubbe, Papageorgiou 2018). It is commonly believed that it seems easier to supervise students or write articles after attaining these qualifications. The purpose of this study was to investigate the barriers that are encountered by academics from a chartered accountancy background to engage in scholarly activities willingly. A qualitative research approach was followed in this study and data was collected by means of interviews. The population was accounting academics at the North-West University. The analysis of data was done qualitatively by means of thematic analysis. The findings revealed barriers such as not knowing where to start due to lack of background or knowledge in conducting research, time, workload, lack of management and lack of access to experienced mentors.